Pengembangan Model Pembelajaran Berbasis Proyek (Project Based Learning) Untuk Meningkatkan Sikap Peduli Lingkungan Pada Anak Usia Dini - Uum Suminar; Yus Alvar Saabighoot; Esya Anesty Mashudi; Maman Rumanta; Ika Rizqi Meilya (Peneliti.net, 2022)
This study aims to conduct a limited trial of a hypothetical project-based learning (PjBL) model to increase environmental awareness in early childhood. This research uses Research and Developmentnet. The research subjects were teachers and early childhood students from kindergartens in Serang City who were determined through a multistage cluster sampling technique. The data in this study were collected through questionnaires, observations, interviews, FGDs and documentation/literature studies. Research data analysis was carried out through data analysis on the development of a hypothetical model and testing the effectiveness of the model. The results of limited trials of project-based learning models to improve environmental care attitudes in early childhood were declared feasible and effective. The feasibility of the learning model was assessed by material experts to get the